Effect of high-dose glucocorticoids on markers of inflammation and bone metabolism in patients with primary glomerular disease - Katarzyna Pęczek; Michał Nowicki (Karger Publishers, 2022)
Background: Glucocorticoids are one of the most commonly used drugs for treatment of inflammatory and autoimmune diseases. Sirtuin-1 (SIRT-1) belongs to family of proteins involved in protection against inflammation and oxidative stress. A role of SIRT-1 in regulation of bone metabolism during high-dose steroid therapy is unknown. Objectives: The study assessed influence of high doses of intravenous corticosteroids on plasma inflammation and bone markers in patients with primary glomerular disease. Methods: The study included 40 patients (25 M, 15 F; mean age 53.1±14 years) with chronic kidney disease (mean estimated glomerular filtration rate (eGFR) 58.9±31.3 ml/min). The main inclusion criterion was clinical and histopathological diagnosis of primary glomerular disease and urine protein excretion >2.0 g/24h. The patients received intravenous pulses of methylprednisolone 20-30 mg/kg/day for three consecutive days followed by oral prednisone 0.8-1.0 mg/kg/day. The blood was taken before administration of methylprednisolone to assess plasma SIRT-1, sclerostin, calcium, phosphate and parathormone (PTH) and first morning urine sample was taken for measurement of calcium, phosphate and albumin to creatinine ratio. The same laboratory tests were repeated after 4, 7 and 30 days during steroid therapy. Results: Plasma SIRT-1 increased significantly during steroid administration. Plasma sclerostin did not change significantly. There was a significant linear negative correlation between changes of SIRT-1 levels and sclerostin throughout the study. In a multiple regression model changes of plasma sclerostin induced by steroid therapy explained the largest part of variance of respective changes of plasma SIRT-1. Conclusions: Plasma SIRT-1 increase during high-dose corticosteroid therapy is negatively related to the change of plasma sclerostin that may suggest a protective role of SIRT-1 against the negative effects of steroid therapy on bone.